Fertility decision and its associated factors in Sub-Saharan Africa: a multilevel multinomial logistic regression analysis - Achamyeleh Birhanu Teshale; Misganaw Gebrie Worku; Getayeneh Antehunegn Tesema (BMC, 2022)
Abstract Background Fertility desire is one of the predictors of contraceptive behavior and fertility-related outcomes. However, information is scarce on individual and community-level factors of women's fertility decisions in sub-Saharan Africa. Objective To assess fertility decisions and their associated factors in Sub-Saharan Africa. Methods The 35 Sub-Saharan African country's most recent demographic and health surveys (DHS) data conducted from 2008 to 2020 was used. A total of 284,744 (weighted) married women were used for analysis. The proportion of fertility decisions with their 95%CI was estimated. To assess the factors associated with fertility decisions, both random effect and fixed effect analyses were conducted. In the fixed analysis, particularly in the multivariable analysis, adjusted relative risk ratio (aRRR) with its 95% confidence interval (CI) was reported and variables with a p-value < 0.05 were considered significant predictors of fertility decisions. Results In this study, 64.35% (95%CI: 64.2%, 64.5%) of the study participants had fertility desire. However, 5.4% (95%CI: 5.3, 5.5) of the study participants had undecided fertility behavior. In the multivariable analysis, desire for more children and undecided fertility desire were relatively lower among older women, women with primary, secondary, and higher education, working women, women who currently use contraceptives, women with a higher number of living children, women with higher parity, women from eastern and southern Africa, and women from wealthy households. While, the ideal number of children, women who had decision-making autonomy, and women from the rural residence were all associated with a relatively higher desire for more children and undecided fertility desire. Furthermore, respondents' education and sex of household head were associated with the desire for more children while media exposure was associated with undecided fertility desire. Conclusion In this study, around two-thirds of women had a desire for more children and only 5.4% of women had undecided fertility desires. Both individual and community-level factors were associated with both desires for more children and undecided fertility desires. As a result, the aforementioned factors should be considered while developing reproductive health programs.